Acquired and intrinsic resistance in cancer immunotherapy - Kelderman, Sander (Mol Oncol, 2014)
A number of immunotherapies, in particular immune checkpoint targeting antibodies and adoptive T‐cell therapies, are starting to transform the treatment of advanced cancers. The likelihood to respond to these immunotherapies differs strongly across tumor types, with response rates for checkpoint targeting being the highest in advanced melanoma, renal cell cancer and non‐small cell lung cancer. However, also non‐responsiveness is observed, indicating the presence of intrinsic resistance or naturally acquired resistance. In addition, a subgroup of patients that do initially respond to immunotherapy will later recur, thereby also pointing towards a role of therapy‐induced acquired resistance. Here, we review our current understanding of both intrinsic and acquired resistance mechanisms in cancer immunotherapy, and discuss potential strategies to overcome them.